PENERAPAN MODEL PEMBELAJARAN CONTEKSTUAL TEACHING AND LEARNING (CTL) PADA KONSEP PERISTIWA SEKITAR PROKLAMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SD NEGERI 23 HALMAHERA BARAT - Lila, Haryati (Universitas Khairun, 2024)
The aim of this research is to identify the process of applying the Contextual Teaching And Learning (CTL) model in improving social studies learning outcomes on the concept of events surrounding the proclamation and to determine the results of the contextual teaching and learning (CTL) model in improving social studies learning outcomes on the concept of events surrounding the proclamation. This research is classroom action research (PTK). The subjects in this research were 15 class II students at SD Negeri 23 West Halmahera. The data analysis technique in this research was carried out in three stages, namely determining individual student learning outcomes, determining classical student learning outcomes and calculating the percentage of student and teacher activity results.The results of the research show that the learning outcomes of class II students at SD Negeri 23 West Halmahera using the Contextual Teaching and Learning (CTL) learning model on the concept of events surrounding the proclamation have increased. This can be seen from the completion scores of cycles I and II, in cycle I the students who were declared complete individually were 3 students with a completeness percentage score of 20%, while those who had not yet completed were 12 students or 80%. Furthermore, in cycle II there was an increase to 14 students who were declared complete from a total of 15 students with a percentage value reaching 93.33%, while 1 student or 6.67% had not yet completed. And teacher activity in cycle I in learning reached an average value of 52.27% and student activity reached an average value of 62.50%, while in cycle II there was an increase in teacher activity in learning reaching an average value of 93.18% and student activities reached an average score of 93.75%.